Design and Construction of a 50m Single Span Ultra High Performance Ductile Concrete Composite Road Bridge - Yen Lei, Voo -; Augustin, Patrick C; Thamboe, Thomas A. J. (International Journal of Sustainable Construction Engineering and Technology, 2012)
A single span 50m long prestressed road bridge was constructed under Public Works Department in the State of Negeri Sembilan, Malaysia contract recently. The bridge was constructed at a small village, Kampung Linsum, crossing a river, Sungai Linggi. To date, this bridge is the Malaysia first and may also be the world longest composite road bridge which made from ultra-high performance ductile concrete (UHPdC). This paper presents the feature of the UHPdC precast girder; brief in-sight of the manufacturing of the girder; the construction sequence of the bridge; the design method and lastly the environmental impact calculation. The midspan deflections of the bridge at different construction history were compared against the collected field data and it showed that the calculated values generally agree well with the field data.